Exosomes Secreted by Adipose-Derived Stem Cells Contribute to Angiogenesis of Brain Microvascular Endothelial Cells Following Oxygen–Glucose Deprivation In Vitro Through MicroRNA-181b/TRPM7 Axis - Yang, Yujia; Cai, Yue; Zhang, Yuan; Liu, Juan; Xu, Zhiqiang (Journal of molecular neuroscience, 2018)
Adipose-derived stem cells (ADSCs) have been demonstrated to promote cerebral vascular remodeling processes after stroke. However, the exact molecular mechanism by which ADSCs exert protective roles in ischemic stroke is still poorly understood. In this study, we identified the role of exosomal microRNA-181b-5p (181b-Exos) in regulating post-stroke angiogenesis. The results of migration assay and capillary network formation assay showed that exosomes secreted by ADSCs (ADSCs-Exos) promoted the mobility and angiogenesis of brain microvascular endothelial cells (BMECs) after oxygen-glucose deprivation (OGD). Quantitative real-time polymerase chain reaction (qRT-PCR) showed that microRNA-212-5p (miR-212-5p) and miR-181b-5p were upregulated in BMECs subjected to the brain extract of the middle cerebral artery occlusion rats. The migration distance and tube length were increased in BMECs cultured with 181b-Exos. Furthermore, we identified that transient receptor potential melastatin 7 (TRPM7) was a direct target of miR-181b-5p. TRPM7 mRNA and protein levels were declined in BMECs cultured with 181b-Exos, but not in BMECs cultured with 212-Exos. Overexpression of TRPM7 reversed the effects of 181b-Exos on migration and tube formation of BMECs. In addition, 181b-Exos upregulated the protein expression of hypoxia-inducible factor 1α and vascular endothelial cell growth factor, and downregulated the protein expression of tissue inhibitor of metalloproteinase 3. The regulatory effect of 181b-Exos was attenuated by overexpressing TRPM7. Altogether, ADSCs-Exos promote the angiogenesis of BMECs after OGD via miR-181b-5p/TRPM7 axis, suggesting that ADSCs-Exos may represent a novel therapeutic approach for stroke recovery.